Investigation of Serum Human Epididymitis Protein 4 Level in Rats with Experimental Acute Pancreatitis - Acar, Ali; Ellidağ, Hamit Yaşar; Balaban, Kadir; Öcal, Serkan; Aslaner, Arif; Çakır, Tuğrul (Turkish Journal of Gastroenterology, 2023)
Backgorund: We aimed to show whether the serum level of Human Epididymitis Protein 4 increases in rats with an experimental acute pancreatitis model created by cerulein. Methods: This study included 24 male Sprague–Dawley rats which were randomly divided into 4 groups each containing 6 rats. Control: the group treated with saline, Group 1: pancreatitis group created with cerulein at a total dose of 80 µg/kg, Group 2: pancreatitis group created with cerulein at a total dose of 120 µg/kg, Group 3: pancreatitis group created with cerulein at a total dose of 160 µg/kg. Results: There were statistically significant differences between edema, acinar necrosis, fat necrosis, and perivascular inflammation scores among the study groups. While the degree of all histopathological findings is lowest in the control group, pancreatic parenchyma damage increases as the amount of injected cerulein increases. There was no statistically significant difference between alanine aminotransferase, aspartate aminotransferase, and Human Epididymis Protein 4 values between study groups. On the other hand, there was a statistically significant difference between amylase and lipase values. The lipase value of the control group was significantly lower than the lipase value of the second and third groups. The amylase value of the control group was significantly lower than all other groups. The highest Human Epididymis Protein 4 value was measured as 104 pmol/L in the first pancreatitis group, where the severity of pancreatitis was mild. Conclusions: In the present study, it was concluded that the Human Epididymis Protein 4 value increased in the case of mild pancreatitis, but there is no correlation between the severity of pancreatitis and the Human Epididymis Protein 4 value. Cite this article as: Acar A, Ellidağ HY, Balaban K, Öcal S, Aslaner A, Çakır T. Investigation of serum human epididymitis protein 4 level in rats with experimental acute pancreatitis. Turk J Gastroenterol. 2023;34(6):665-671.